Economic feasibility of ground-based steep slope logging using winch-assist technologies - Goodman, Justin C. (My University, 2018)
This thesis examines the use of winch-assist technologies in logging operations in the interior of British Columbia. The data used for this thesis is from a contractor’s (located in Central B.C.) professional judgment as well as from other studies that took place near this area. The objective of this thesis was to determine the economic feasibility of winch-assist logging systems and compare the cost ($/m3) to cable yarding systems. Comparisons between systems were made using a costing model that determined the total cost of wood to roadside for three different systems including; winch-assist, cable yarding with manual falling and cable yarding with mechanized felling. In addition, a sensitivity analysis was used to determine how sensitive cost was to a variety of variables. The analysis done is within the reasonable scope of the requirements of an undergraduate thesis.The results found that cost ($/m3) was most sensitive to productivity and machine utilization. A key finding of this thesis was cable yarding systems with mechanized felling had the lowest overall cost. The implications of the results and the applications of winch-assist logging systems are discussed further throughout the thesis.
Keywords: Winch-assist technologies; Steep slope logging; Mechanized logging; Cable yarding